Pengaruh pH dan Temperatur Terhadap Kinerja Elektrroda Selektif Ion (ESI) Timbal(II) Tipe Kawat Terlapis Berbasis S-Methyl N-(Methylcarbamoyloxy) Thioacetimidate - Putra, Ilham Krisdarmawan; Fardiyah, Qonitah; Sulistyati, Hermin (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
Ion selective electrode (ISE) lead(II) based coated wire type with S-methyl N-(methylcarbamoyloxy) thioacetimidate as the ionofor, polyvinylchloride (PVC) as the polymer matrix and dioktilftalat (DOP) as plasticizer has been developed. The ISE lead(II) showed Nernstian slope of 29,26 mV/decade of concentration, linear concentration range of 10-5 – 10-1 M, detection limit of 1,185 x 10-5 M or equal to 2,453 ppm of lead, and response time of 60 seconds. The purpose of this research is to study the effect of pH and temperature on the performance (ISE) lead(II) based coated wire type S-methyl N-(methylcarbamoyoxy) thioacetimidate. Effect of pH and temperature on the performance of  ISE lead(II) was determined by measuring the potential response of lead(II) solution using acetate buffer at pH 2-8 and temperature of 20-50 oC. The results showed that the performance of ISE lead(II) based coated wire type S-methyl N-(methlcarbamoyloxy) thioacetimidate was optimum at pH 7 and was not influenced by the temperature from 20-50 oC.